Innovations and Barriers in Telehealth for Maternal and Child Health: A Global Analysis - Mizawat, Afrina (Medicor : Journal of Health Informatics and Health Policy, 2025)
Telehealth has emerged as a transformative solution in maternal and child health (MCH), particularly in the wake of the COVID-19 pandemic. This narrative review aims to synthesize recent innovations and identify systemic barriers that influence telehealth adoption in MCH contexts globally. Literature was sourced from PubMed, Scopus, CINAHL, and Google Scholar, focusing on studies published in the past decade involving telehealth interventions targeting pregnant women, postpartum mothers, and children under five. Findings highlight that digital innovations such as mobile health applications, SMS reminders, and teleconsultations enhance antenatal care attendance, reduce perinatal mortality, and improve postpartum mental health and breastfeeding outcomes. However, significant challenges persist, including limited infrastructure, digital illiteracy, and socio-cultural resistance—especially in low- and middle-income countries. The review underscores the importance of inclusive policy frameworks, adequate funding, and healthcare workforce readiness in supporting equitable telehealth implementation. Future research should prioritize long-term impact evaluation and culturally tailored strategies to promote sustainable adoption.